Patterns of Potentially Inappropriate Bladder Antimuscarinic Use in People with Dementia: A Retrospective Cohort Study - Ariel R. Green; Jodi Segal; Cynthia M. Boyd; Jin Huang; David L. Roth (Adis, Springer Healthcare, 2020)
Abstract Background Emergency department (ED) visits or hospitalizations should prompt review of the patient's medications after discharge and targeted deprescribing to reduce ongoing risks. Objective To see if this is happening, we sought to examine the proportion of serious falls and delirium that were followed by a prescription fill for a bladder antimuscarinic. Our secondary objective was to identify concurrent use of other anticholinergics, cholinesterase inhibitors (ChEIs), and diuretics among people with dementia taking bladder antimuscarinics. Methods Retrospective descriptive study using data from the National Health and Aging Trends Study (2011-2014) linked with Medicare claims from 2010-2014. The primary outcome was the proportion of serious falls or delirium that were followed by a bladder antimuscarinic prescription fill within 12 months. The secondary outcome was the proportion of individuals concurrently receiving prescriptions for bladder antimuscarinics, other strong anticholinergics, ChEIs, and diuretics. Results During the observation period, 8.88% of people with dementia filled a bladder antimuscarinic prescription. Over one-third (35%) initiated use after being identified as having dementia. Many used bladder antimuscarinics concurrently with other strong anticholinergics (19%), diuretics (42%), and ChEIs (32%). The majority (76%) of serious falls or delirium among people with dementia and bladder antimuscarinic use were followed by a bladder antimuscarinic prescription within 12 months. Conclusions In this descriptive study, bladder antimuscarinic prescriptions were often filled irrespective of dementia status, serious falls, or delirium. Concurrent use of other anticholinergics, diuretics, and ChEIs was common. Falls and delirium should trigger review of the medication list after discharge and targeted deprescribing in people with dementia.